The Effect Growth Opportunity, Net Working Capital, Cash Conversion Cycle and Tax Avoidance on Cash Holding Companies (Case Study on LQ 45 Index Companies 2018-2020) - Rakan Adi Fawwazin (Global Accounting, 2022)
Cash Holding is the element of the company's assets that is considered the most liquid can be in the form of cash needed to meet the needs of daily operational activities and is known for its ease of turning into cash used for the purposes of company transactions such as paying debts, paying dividends, paying salaries or wages, and buying fixed assets. Good Cash Holding is an optimal Cash Holding, where there is no excess or deficiency. The study aims to obtain empirical evidence about the effect of Net Working Capital, Growth Opportunity, Tax Avoidance and Cash Conversion Cycle on Cash Holding. Net Working Capital, Tax Avoidance, Growth Opportunity and Cash Conversion Cycle are the independent variables used, while Cash Holding is the dependent variable used. The researchers concluded that partially Growth Opportunity and Tax Avoidance did not have a significant effect on Cash Holding. Meanwhile Cash Conversion Cycle and Net Working Capital have a significant influence on Cash Holding. Simultaneous research results Cash Conversion Cycle, Growth Opportunity, Net Working Capital, and Tax Avoidance have a significant influence on Cash Holding in LQ 45 Index companies on the Indonesia Stock Exchange in 2018-2020.